Cohesion and Coherence Analysis of Solo Baru Billboards - Hidayah, Arini; Purnomo, Budi; Tri Widarwati, Nunun (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2023)
This study uses a discourse analysis approach on Solo Baru billboards. The purpose of this study was to describe the microstructural analysis of Solo Baru billboards. This research is descriptive qualitative research. Data collection in this study was carried out using the method of listening and documentation. The research data was taken from billboards in Solo Baru. The results of this study indicate the existence of cohesion and coherence tools in the discourse of Solo Baru billboards. The types of cohesion found were references (5 data), ellipsis (24 data), repetition (7 data), hyponymy (3 data), and collocation (6 data). The type of coherence found there is a relationship between the meaning of addition (6 data), cause (5 data), effect (5 data), and the relationship between requirements and presuppositions (4 data), and time (2 data).